STATUS HUKUM KEBERADAAN ASET BEKAS MILIK ASING/TIONGHOA (ABMA/T) DI PROVINSI SUMATERA UTARA - Jusak Tarigan; Bismar Nasution; Faisal Akbar Nasution; Mahmul Siregar (Universitas Sumatera Utara, 2015)
ABSTRACT Legal provisions regulate the management of the State assets in Articles 23, 23A, 23B, 23C, and 23D of the 1945 Constitution which includes APBN (State Budget), Tax, and other Revenues. Law No. 17/2003 and Law No. 1/2004 which regulate State finance that includes all right and obligation of the State can be valued by money, including all kinds of money and goods, including all goods bought or obtained by APBN/D or come from other legal sources. The legal status of ABMA/T owned by individuals (third party) and the certificate has been obtained from BPN do not guarantee that it is absolute although land registration is intended to guarantee legal certainty. In this case, the principles of negative, recent, and formal and material truth are used. The obstacles found by the team are as follows: assets are not found, the third party has obtained certificate from BPN, difference in area, shift in function, the team is not professional, lack of proactive, asset is in remote place, claim from the third party, and the problem with compensation. Keywords: Developing Legal Status, ABMA/T, Assistance Team, State Assets/ State Financial, DJKN Sumut